Pengaruh Komunikasi Terhadap Kepercayaan (Studi Pada UMKM Di Daerah Istimewa Yogyakarta) - cahya purnama asri (Universitas Mercu Buana, 2021)
This study aims to determine the effect of communication on trust in MSMEs in the Special Region of Yogyakarta (DIY). This research was conducted on 50 MSME owners in DIY, which were determined by the purposive sampling method. Data analysis in this study used linear regression. The results of the study indicate that there is no effect of communication on trust. Suggestions for further research are also presented here